Four brothers [videorecording (DVD)] - Singleton, John, 1968-2019-; Wahlberg, Mark, 1971-; Tyrese; Andre 3000, 1975-; Hedlund, Garrett, 1985-; Howard, Terrence (Paramount Pictures, 2005)
Four adopted brothers come back home to avenge their mother's death at what appeared to be a random killing in a grocery store robbery. However, the boy's investigation of the death reveals more nefarious activities involving the one brother's business dealings with a notorious local gangster. Two local cops, who are trying to solve the case, may also not be what they seem.